2002
DOI: 10.1038/sj.ejcn.1601431
|View full text |Cite
|
Sign up to set email alerts
|

Operationalization of food consumption surveys in Europe: recommendations from the European Food Consumption Survey Methods (EFCOSUM) Project

Abstract: Background: The EFCOSUM (European Food Consumption Survey Methods) Project aims at harmonizing food consumption surveys in European countries within the perspective of an overall Public Health Monitoring Programme. Harmonization implies the need for a common framework of procedures and tools, that are applicable and feasible in all potentially interested countries. A major element in such a framework is the protocol for the operationalization of a food consumption survey, referring to all practical, logistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…The chosen setting of two times 4 days of recording caused an overlap of Wednesdays and Saturdays. It is known that food consumption differs between weekdays and weekends [12,15,16]. Internal analyses showed that intakes of energy and carbohydrates on Saturdays were significantly higher than the intakes on weekdays (data not shown).…”
Section: Weighed Food Recordsmentioning
confidence: 93%
“…The chosen setting of two times 4 days of recording caused an overlap of Wednesdays and Saturdays. It is known that food consumption differs between weekdays and weekends [12,15,16]. Internal analyses showed that intakes of energy and carbohydrates on Saturdays were significantly higher than the intakes on weekdays (data not shown).…”
Section: Weighed Food Recordsmentioning
confidence: 93%
“…They should be familiar with the nutritional habits (eg the foods usually eaten together) to be able to get detailed and complete answers and to control the accuracy of data. For an efficacious elaboration and evaluation, a coding system of foodstuffs and meals, and also a computerized program are needed (Beaton et al, 1979;Nelson & Bingham, 1997;De Henauw et al, 2002;Slimani & Valsta, 2002). Due to intra-individual variability, a single 24 h recall does not represent the usual individual intake but it characterizes the average intake of a group or population fairly well.…”
Section: The 24 H Dietary Recallmentioning
confidence: 99%
“…23 However, it is rarely applied as a proxy instrument, as was planned for the IDEFICS study, which posed additional challenges to its development and application. The SACINA software can be administered in different ways (for example, as a face-to-face interview or as a self-administered interview) to collect dietary intake information.…”
Section: Discussionmentioning
confidence: 99%